Conceitos e aplicações da energia solar para o ensino médio - Gil, Santiago Maia (2023)
This research explores the technological education focused on Solar Energy within the context of high school education. As an outcome of this work, an educational product was developed in the form of a book titled "Concepts and Applications of Solar Energy for High School." This book, designed for teachers seeking supplementary materials and methodologies on the subject, is divided into three main sections: the first provides a conceptual and contextualized introduction to Brazil's energy landscape, emphasizing the country's solar potential and the technologies related to converting solar radiation into electricity and heat; the second section delivers a detailed guide for assembling educational kits, highlighting a parabolic solar concentrator, an explanatory panel on the components of a photovoltaic system, and a mini solar pumping system; finally, the third section offers guidance on the use of commercial educational objects, aiming to enrich the teaching and learning process through playful tools, such as the Crookes Radiometer, the portable spectroscope, and mini solar-powered cars. The literature review underscored the importance and pressing need to disseminate knowledge and innovations associated with solar energy, particularly given the growing awareness of energy consumption and contemporary environmental challenges. The proposed methodology was successfully implemented among students of the mid-level technical course in Constructions at the Federal Institute of Bahia, Euclides da Cunha campus, using the research-intervention method. Results demonstrated that students were able to assimilate and reinterpret concepts and applications related to the topic, emphasizing the significance of this project in encouraging sustainability and promoting renewable energy sources in the educational setting.